Investing the anti epileptic effect of Aqueous extract of Artemisia absinthium on seizures induced by pentylenetetrazole in male rats - Masoumeh Gholami; Mehdi Sadegh (Complementary Medicine Journal of Faculty of Nursing and Midwifery)
Introduction:Epilepsy is one of the most common neurological disorders that affect social, economic, and biological aspects of human life. Thus, this study aimed to investigate the effect of Aqueous extract of Artemisia absinthium on PTZ-induced seizures in male rats.